Genome analysis and description of Xanthomonas massiliensis sp. nov., a new species isolated from human faeces. (November 2018) - Ndongo, S.; Beye, M.; Dubourg, G.; Nguyen, T.T.; Couderc, C.; Fabrizio, D.P.; Fournier, P.-E.; Raoult, D.; Angelakis, E.
Abstract: Xanthomonas massiliensis strain SN6 T is a Gram-negative bacterium which is aerobic, motile and nonsporulating. This new species isolated from human faeces exhibited the characteristic traits of members of this genus, such as yellow pigmentation and viscosity. Here we present the main phenotypic characteristics and the taxonogenomics description of this strain. The genome is 3 690 720 bp long with DNA G + C content of about 70.52%.